Role of Multifocal Visually Evoked Potential as a Biomarker of Demyelination, Spontaneous Remyelination, and Myelin Repair in Multiple Sclerosis - Klistorner, Alexandr; Graham, Stuart L. (Frontiers in Neuroscience, 2021)
Multiple sclerosis (MS) is a complex disease of the central nervous system (CNS), characterized by inflammation, demyelination, neuro-axonal loss, and gliosis. Inflammatory demyelinating lesions are a hallmark of the disease. Spontaneous remyelination, however, is often incomplete and strategies that promote remyelination are needed. As a result, accurate and sensitive in vivo measures of remyelination are necessary. The visual pathway provides a unique opportunity for in vivo assessment of myelin damage and repair in the MS-affected brain since it is highly susceptible to damage in MS and is a very frequent site of MS lesions. The visually evoked potential (VEP), an event-related potential generated by the striate cortex in response to visual stimulation, is uniquely placed to serve as a biomarker of the myelination along the visual pathway. The multifocal VEP (mfVEP) represents a most recent addition to the array of VEP stimulations. This article provides a current view on the role of mfVEP as a biomarker of demyelination, spontaneous remyelination, and myelin repair in MS.